Blood eosinophils and response to maintenance chronic obstructive pulmonary disease treatment: data from the FLAME trial - Roche, Nicolas; Herth, Felix (American journal of respiratory and critical care medicine, 2017)
Rationale: Post hoc analyses suggest that blood eosinophils have potential as a predictive biomarker of inhaled corticosteroid efficacy in the management of chronic obstructive pulmonary disease (COPD).Objectives: We prospectively investigated the value of blood eosinophils as a predictor of responsiveness to an inhaled corticosteroid/long-acting β2-agonist combination versus a long-acting β2-agonist/long-acting muscarinic antagonist combination for exacerbation prevention.Methods: We conducted prespecified analyses of data from the FLAME (Effect of Indacaterol Glycopyronium vs Fluticasone Salmeterol on COPD Exacerbations) study, which compared once-daily long-acting β2-agonist/long-acting muscarinic antagonist indacaterol/glycopyrronium 110/50 μg with twice-daily long-acting β2-agonist/inhaled corticosteroid salmeterol/fluticasone combination 50/500 μg in patients with one or more exacerbations in the preceding year. Subsequent post hoc analyses were conducted to address further cutoffs and endpoints.Measurements and Main Results: We compared treatment efficacy according to blood eosinophil percentage (<2% and ≥2%, <3% and ≥3%, and <5% and ≥5%) and absolute blood eosinophil count (<150 cells/μl, 150 to <300 cells/μl, and ≥300 cells/μl). Indacaterol/glycopyrronium was significantly superior to salmeterol/fluticasone for the prevention of exacerbations (all severities, or moderate or severe) in the <2%, ≥2%, <3%, <5%, and <150 cells/μl subgroups, and at no cutoff was salmeterol/fluticasone superior to indacaterol/glycopyrronium. Furthermore, the rate of moderate or severe exacerbations did not increase with increasing blood eosinophils. The incidence of pneumonia was higher in patients receiving salmeterol/fluticasone than indacaterol/glycopyrronium in both the <2% and ≥2% subgroups.Conclusions: Our prospective analyses indicate that indacaterol/glycopyrronium provides superior or similar benefits over salmeterol/fluticasone regardless of blood eosinophil levels in patients with COPD.Clinical trial registered with www.clinicaltrials.gov (NCT01782326).